Russia Economic Report, No. 46, December 2021 : Amidst Strong Economic Recovery, Risks Stemming from COVID-19 and Inflation Build - World Bank (World Bank, Washington, DC, 2022)
Russia saw strong growth in 2021, with momentum weakening late in the year. Growth will slow as Russia battles COVID-19 and elevated inflation. Globally, environmental sustainability is becoming central to the economic agenda. The challenge for Russia is to fundamentally transform its economic structure.